The cave of Aaaaah! Doom! - Kent, Jaden; Bodnaruk, Iryna (New York Little Bee Books, 2017)
A young dragon named Ella convinces her twin brother Owen to join her on a bold quest to find a wizard that will help cure Owen of his flaming cold.
b
b
Keywords: Dragons -- Fiction; Siblings -- Fiction; Twins -- Fiction; Adventure and adventurers -- Fiction; Magic -- Fiction; Humorous stories